Multiplex Immunoassay Platforms Based on Shape-Coded Poly(ethylene glycol) Hydrogel Microparticles Incorporating Acrylic Acid - Park, Saemi (Molecular Diversity Preservation International (MDPI), 2012)
A suspension protein microarray was developed using shape-coded poly(ethylene glycol) (PEG) hydrogel microparticles for potential applications in multiplex and high-throughput immunoassays. A simple photopatterning process produced various shapes of hydrogel micropatterns that were weakly bound to poly(dimethylsiloxane) (PDMS)-coated substrates. These micropatterns were easily detached from substrates during the washing process and were collected as non-spherical microparticles. Acrylic acids were incorporated into hydrogels, which could covalently immobilize proteins onto their surfaces due to the presence of carboxyl groups. The amount of immobilized protein increased with the amount of acrylic acid due to more available carboxyl groups. Saturation was reached at 25% v/v of acrylic acid. Immunoassays with IgG and IgM immobilized onto hydrogel microparticles were successfully performed with a linear concentration range from 0 to 500 ng/mL of anti-IgG and anti-IgM, respectively. Finally, a mixture of two different shapes of hydrogel microparticles immobilizing IgG (circle) and IgM (square) was prepared and it was demonstrated that simultaneous detection of two different target proteins was possible without cross-talk using same fluorescence indicator because each immunoassay was easily identified by the shapes of hydrogel microparticles.